Development and Initial Validation of the Student Interest and Choice in STEM (SIC-STEM) Survey 2.0 Instrument for Assessment of the Social Cognitive Career Theory Constructs - Roller, Sarah A.; Lampley, Sandra A.; Dillihunt, Monica L.; Benfield, Michael P. J.; Gholston, Sampson E.; Turner, Matthew W.; Davis, Andrew M. (Journal of science education and technology, 2020)
In response to a growing need for STEM professionals, this study reports the results of the initial validation of a refined survey instrument that purports to measure the five constructs of the social cognitive career theory framework within the subjects of mathematics, science, engineering and technology. To investigate the instrument’s reliability and psychometric properties, we administered this 45-item survey to students in grades 4–12. Reliability and validity (content and construct) were assessed using Cronbach’s coefficient alphas and structural equation modeling. Path coefficients for the five constructs indicated weak to moderate influences on the subscales, and the goodness-of-fit indices demonstrated that the model is acceptable. Initial results indicate the survey has the potential to collect reliable and valid data and suggest the instrument may be helpful in measuring students’ interests and choices in STEM careers for research, partnerships, and curricular development. Additionally, results highlight two areas for further investigation, which include the impact conscientious or random responders have on the survey’s psychometric properties and what constitutes satisfactory Cronbach’s alpha for results to be interpreted in a significant way.